Follow-up and reoperations after repair of Chronic Aortic Dissection Type A (CADA) - Karck, Matthias; Laas, Joachim; Heinemann, Markus K.; Borst, Hans Georg (Langenbecks Archiv für Chirurgie, 1990)
SummaryBetween 4/78 und 9/89 44 patients (pts.) underwent primary repair of CADA. 3 pts. died early postoperatively. 36 pts. were followed-up 3 months to 9.7 years (x;̄ = 3.1 years) postoperatively with CT, DSA and echocardiography. 8 pts. underwent 12 aortic reoperations, in 10 cases due to persistent or recurrent aneurysms. Conclusions: In CADA radical replacement of the Ascending Aorta is advisable to prevent recurrent aneurysms formation. Systematic follow-up facilitates early recognition and repair of progressively chronic or new downstream aortic pathology.